Sustainable Development of Elevated Shell Platform - Azizah, Abdul Nassir; Min, Yee Hooi; Syahrul Fithry, Senin; Peen, Woo Yian (Chulalongkorn University, 2021)
Shell structure has a unique thin, curved plate shaped yet strong enough to transmit applied forces by compressions but only being constructed as a roof structure with minor external load applied onto it. The objectives of this research are to study the feasibility in proposing elevated shell platforms in resisting heavy loading, to investigate the effect of shell geometric on elevated shell platforms and to identify the suitable shell geometric as economic and sustainable in construction development. Five different geometries of shell structure have been proposed which are dome, cone, pendentive, clam shape and leaf-like shape. LUSAS software has been used to analyze the different geometries of the shell and study the effect of stresses and deformation. The optimum height was determined by convergence test and proceeded to the modelling phase to obtain the output of stresses. In findings, this study has justified that the elevated shell platform is feasible to be applied in sustainable industry development and the effect of each different geometric has been identified by stress comparison. Most suitable geometric which is toroidal has been determined by extracting the least value of maximum stresses produced, with the optimum surface area provided to accommodate the maximum load applied.